GhCLCg-1, a Vacuolar Chloride Channel, Contributes to Salt Tolerance by Regulating Ion Accumulation in Upland Cotton - Liu, Wei; Feng, Junping; Ma, Wenyu; Zhou, Yang; Ma, Zongbin (Frontiers in Plant Science, 2021)
Soil and freshwater salinization is increasingly becoming a problem worldwide and has adversely affected plant growth. However, most of the related studies have focused on sodium ion (Na+) stress, with relatively little research on chloride ion (Cl–) stress. Here, we found that upland cotton (Gossypium hirsutum) plants accumulated Cl– and exhibited strong growth inhibition under NaCl or KCl treatment. Then, a chloride channel gene (GhCLCg-1) was cloned from upland cotton. Phylogenetic and sequence analyses indicated that GhCLCg-1 was highly homologous to AtCLCg and also have conserved voltage_CLC and CBS domains. The subcellular localization assay showed that GhCLCg-1 was localized on the vacuolar membrane. Gene expression analyses revealed that the expression of GhCLCg-1 increased rapidly in cotton in response to chloride stress (NaCl or KCl), and the transcript levels increased as the chloride stress intensified. The overexpression of GhCLCg-1 in Arabidopsis thaliana changed the uptake of ions with a decrease of the Na+/K+ ratios in the roots, stems, and leaves, and enhanced salt tolerance. In contrast, silencing GhCLCg-1 in cotton plants increased the Cl– contents in the roots, stems, and leaves and the Na+/K+ ratios in the stems and leaves, resulting in compromised salt tolerance. These results provide important insights into the toxicity of chloride to plants and also indicate that GhCLCg-1 can positively regulates salt tolerance by adjusting ion accumulation in upland cotton.